Heme oxygenase-1 suppresses the apoptosis of acute myeloid leukemia cells via the JNK/c-JUN signaling pathway. Issue 5 (May 2015) - Lin, Xiaojing; Fang, Qin; Chen, Shuya; Zhe, Nana; Chai, Qixiang; Yu, Meisheng; Zhang, Yaming; Wang, Ziming; Wang, Jishi
Highlights Heme oxygenase-1 (HO-1) is aberrantly overexpressed in the majority of AML patients. HO-1 has an effect on the apoptosis of AML cell lines. Overexpression of HO-1 accelerates leukemia's progression in vivo. HO-1 suppresses the apoptosis of AML cells through activating JNK/c-JUN signaling pathway.